ST8SIA6-AS1 serves as a prognostic biomarker in cancer and exhibits oncogenic properties in prostate cancer - Wen, Yaoan; Yang, Jiangbin; Zhan, Shuyuan; Huang, Yuanjing; Chen, Guoqiang; Zheng, Song; Zhu, Shaoxing (Frontiers in Genetics, 2025)
BackgroundThe prognostic significance of long non-coding RNA ST8SIA6-AS1 remains ambiguous, and its biological role in prostate cancer (PCa) has not been thoroughly investigated. This study seeks to conduct a comprehensive meta-analysis to assess the clinical relevance of ST8SIA6-AS1 across different malignancies, with a particular emphasis on elucidating its functions in the advancement of PCa.MethodsSystematic searches were conducted in the PubMed, Embase, and Web of Science databases to select studies that met the criteria. Data, including hazard ratios (HR) with 95% confidence intervals (95% CI) and clinical pathological parameters, were collected. Subgroup analyses were performed based on sample size and tumor type. The expression profile analysis of PCa tissues was performed using the GTEx and TCGA databases. Changes in cell phenotype were assessed through Transwell migration assays and EdU proliferation assays. Additionally, the biological effects of ST8SIA6-AS1 were validated using an in vivo xenograft tumor model.ResultsThe meta-analysis including 11 studies with a total of 2,392 patients showed that high expression levels of ST8SIA6-AS1 are significantly positively correlated with reduced overall survival in patients with malignant tumors (HR = 1.48, 95% CI: 1.31–1.65), increased tumor size (OR = 2.07, 95% CI: 1.35–3.18), and advanced TNM staging (OR = 2.83, 95% CI: 1.77–4.52). Experimental findings confirmed that ST8SIA6-AS1 expression is significantly upregulated in PCa tissues and cells. Furthermore, the knockdown of ST8SIA6-AS1 inhibited cell migration, invasion, and proliferation in vitro, as well as suppresses cell growth in vivo.ConclusionST8SIA6-AS1, a significant oncogenic lncRNA, could promote disease progression in PCa and could serve as a significant prognostic marker for adverse outcomes in cancer.